Determinants of Technology Acceptance of the Pamong Desa LMS Among Village Officials in West Bandung Regency - Muhamad Nur Fajar; Heri Fathurahman (goodwood publishing, 2026)
Purpose: This study aimed to examine the factors influencing the technology acceptance of the Learning Management System (LMS) Pamong Desa among village officials in West Bandung Regency using the General Extended Technology Acceptance Model for E-Learning (GETAMEL) framework. Methodology: This study employed a quantitative approach with 245 village officials with prior experience using the LMS Pamong Desa. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS), incorporating variables such as experience, subjective norms, enjoyment, computer anxiety, and self-efficacy. Results: The results show that Enjoyment significantly affected perceived usefulness and perceived ease of use, whereas self-efficacy influenced perceived ease of use. Perceived ease of use affects perceived usefulness and intention to use, and perceived usefulness also influences the intention to use. Experience, subjective norms, and computer anxiety were not significant. Conclusions: Intrinsic and cognitive factors are more influential than external and social factors in determining technology acceptance. Limitations: This study was limited to a single regional context and cross-sectional data. Contributions: This study contributes to the literature by demonstrating that the explanatory power of the GETAMEL model is context-dependent rather than universal, particularly in decentralized public sector settings. It highlights that intrinsic and cognitive factors outweigh social influences in shaping technology acceptance, offering new insights into e-learning adoption in local governance environments.